Backcasting frugally innovative smart sustainable future cities - Ebolor, Alexander (Journal of Cleaner Production, 2023)
This paper envisions alternative scenarios for future cities that are resilient environmentally, socially, economically, and embedded in smart infrastructure and governance. It reinforces the position that although complementary, the backcasting approach is more appropriate for future city planning. There is limited research that envisions how future cities can be backcasted with frugal innovation (FI) underpinning the sustainability pillars. This research aims to narrow the gap. The methodology is based on a systematic literature review and secondary exploratory case studies. The results of the TOWS (threats, opportunities, weaknesses, strengths) analysis on the suitability of FI on smart sustainable cities (SSC) developmental policies show that FI is an affordable and inclusive way to sustainably develop cities without injury to the environment. The findings reveal that the five pillars of a smart sustainable future city can integrate frugal innovation and lean engineering concepts to ensure sustainable development at lower costs. Through frugal innovation embedded in city infrastructure, cleaner methods of production can be realized, and inclusiveness can be fostered.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Backcasting; ESG; Frugal innovation; SDGs; Smart sustainable cities; Inklusion

Fostering the Sustainable Development Goals with technologies underpinned by frugal innovation - Ebolor, Alexander; Agarwal, Nivedita; Brem, Alexander (International Journal of Technology Management, 2022)
The race against time to attain the Sustainable Development Goals (SDGs) intensifies, with inequality, poor living conditions, and biodiversity threats still prevalent. Achieving the SDGs is constrained by limited resources that require frugal solutions that are affordable, easy-to-use, ecologically sustainable, and socially inclusive. The role of infrastructure companies developing technologies with a frugal orientation that focus on the 17 SDGs must be at the core of efforts, because sustainable infrastructure is critical to the SGDs. This paper examines how such company-efforts foster the SDGs through the lens of frugal innovation. An exploratory multiple case study methodology was used with a 3-step and 4-dimensional evaluation approach to determine what technologies are fostering the SDGs, and their frugal characteristics. The results show that alternative resource and energy innovations are at the core of how infrastructure companies are promoting sustainability and fostering the SDGs. Most cases cluster around ecological contributions (mainly climate and energy), with sustainability and cost-effectiveness being the common characteristics. Implications for theory and practice are discussed, as well implications for policy-making.
CRIS-Team WoS Importer:2022-04-01
Keywords: Inklusion

Sustainable development in the construction industry: The role of frugal innovation - Ebolor, Alexander; Agarwal, Nivedita; Brem, Alexander (Journal of Cleaner Production, 2022)
The journey towards sustainable development is largely limited by practices in the construction industry, which is a significant generator of wastes and other anthropogenic emissions. It therefore follows that a transition to cleaner construction technologies and methods through the deployment of innovations that minimize the use of resources and anthropogenic pollutants such as greenhouse gasses (GHG), aerosols, carbon dioxide, sulfur oxide, nitrogen oxide, benzene, and other emissions which adversely affect humans and impact the environment will foster the sustainable development goals. To sustainably develop, it is imperative for the construction industry as a hub of economic development to look inwards for solutions that are frugal, pragmatic, and inclusive. The tools for understanding the phenomena investigated are derived from the theories of frugal innovation, sustainable construction, and appropriate technology. The case of Hydraform was studied to understand how it contributes to sustainable development. Semi-structured interviews with industry experts and stakeholders provide qualitative insights into the phenomena investigated. The findings indicate that frugal innovation (FI) in the construction industry is shaped by large institutional players such as state governments, and non-profit organizations (NGOs), while a segment of the target user-groups interpret the innovation as lower-class status artifacts. Specifically, this study contributes to an understanding of how locally-engineered technology can foster development in the bottom of the pyramid (BoP) economies. Practitioners also gain through knowledge of the diffusion inhibitors, and how to navigate the diffusion barriers.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Cleaner production; ESG; Frugal innovation; Hydraform; Sustainable construction; Sustainable development